Coupling of reinforcement with Tuff concrete on quartz sands prepared on Portland cement without additives and with expanding additives - B. H. Beshtokov; A. S. Tsipinov; A. M. Gusenov; A. R. Kazharov; A. A. Cardanov (Вестник Дагестанского государственного технического университета: Технические науки, 2022)
Objective. The study of the adhesion of reinforcement with tuff concrete on quartz sands, prepared both on ordinary Portland cement and expanding additives.Method. The solution is carried out by conducting an experiment, for this purpose, the manufacture and testing of tuff-concrete prisms with one centrally located reinforcing rod of a periodic profile of class A-400 was carried out, within the time limits established by the norms.Result. According to the results of the experiment, it was found that the adhesion of reinforcement to concrete is mainly determined by the compressive strength of concrete. The strength of the reinforcement's adhesion to concrete increases with the increase in the strength of concrete. In the studied compositions, the effect of the concentration of a large (tuff) filler or an expanding additive was not detected.Conclusion. The adhesion of reinforcement to concrete is largely determined by the strength of the concrete itself. The type of binder (the presence of an expanding additive) and the concentration of coarse aggregate do not significantly affect the adhesion of reinforcement to concrete. The dependence between the coupling of reinforcement during punching and the strength of concrete is revealed. An assessment (indirect) of the endurance and crack resistance of the coupling can be given by (the value of the conditional coupling) lsl, determined by the length of the visually visible cut of the consoles on concrete samples during penetration tests. In tuff-concrete of the studied compositions, the lcl decreases with an increase in the strength of concrete. In tuff concrete with RD, the endurance and crack resistance of the coupling turned out to be higher compared to tuff concrete on ordinary Portland cement.